KEANEKARAGAMAN JENIS LICHENES PADA BERBAGAI TINGKAT KETINGGIAN DIKAWASAN HUTAN LINDUNG - Sanjaya, Rizki Ary (Maliki Interdisciplinary Journal, 2025)
This study aims to determine the diversity of lichen species at various altitudes in protected forest areas. Lichens are symbiotic organisms between fungi and algae/cyanobacteria that play an important role in the ecosystem, such as air quality indicators and ecosystem pioneers in nutrient-poor habitats. The research method used field surveys with purposive sampling techniques at three different altitudes: <500 masl, 500–1000 masl, and >1000 masl. Each location was made an observation plot measuring 10 × 10 m, then morphological identification and recording of the number of individuals of each species. Data analysis included the Shannon-Wiener diversity index (H’) and the evenness index (E). The results showed that the highest lichen diversity was found at medium altitudes (500–1000 masl) with an H’ value of 2.85, while the lowest diversity was found at low altitudes (<500 masl) with an H’ value of 1.92. Environmental factors such as humidity, light intensity, and temperature are thought to influence the distribution and abundance of lichens. The conclusion of this study is that altitude influences lichen diversity, where microclimate conditions at medium altitudes are more supportive of the growth and diversity of lichen species.